The Role of the Thioredoxin Detoxification System in Cancer Progression and Resistance - Jovanović, Mirna; Podolski-Renić, Ana; Krasavin, Mikhail; Pešić, Milica (Frontiers in Molecular Biosciences, 2022)
The intracellular redox homeostasis is a dynamic balancing system between the levels of free radical species and antioxidant enzymes and small molecules at the core of cellular defense mechanisms. The thioredoxin (Trx) system is an important detoxification system regulating the redox milieu. This system is one of the key regulators of cells’ proliferative potential as well, through the reduction of key proteins. Increased oxidative stress characterizes highly proliferative, metabolically hyperactive cancer cells, which are forced to mobilize antioxidant enzymes to balance the increase in free radical concentration and prevent irreversible damage and cell death. Components of the Trx system are involved in high-rate proliferation and activation of pro-survival mechanisms in cancer cells, particularly those facing increased oxidative stress. This review addresses the importance of the targetable redox-regulating Trx system in tumor progression, as well as in detoxification and protection of cancer cells from oxidative stress and drug-induced cytotoxicity. It also discusses the cancer cells’ counteracting mechanisms to the Trx system inhibition and presents several inhibitors of the Trx system as prospective candidates for cytostatics’ adjuvants. This manuscript further emphasizes the importance of developing novel multitarget therapies encompassing the Trx system inhibition to overcome cancer treatment limitations.